(untitled) (Journal of Engineering, 2024)
Rutting is one of the most complex and widespread types of distress. The rutting is frequently observed on Iraqi roads, especially at the checkpoints, forming a significant hazard on the asphalt layers. Factors such as heavy loads and high temperatures contribute to this distress. Adding fibers to a hot mix asphalt (HMA) effectively improves performance and extends the lifespan of the flexible pavement. This article used glass, steel, and basalt fibers. The wheel tracking test assessed the fibre-asphalt mixture for rutting resistance and compared it with the mix without adding fibers (control HMA). Meanwhile, the microscopic structure of fibres and asphalt mixture modified with fibers was examined using the Field Emission Scanning Electron Microscopy (FESEM) technique. Steel, glass, and basalt fibers were incorporated into HMA in proportions of 0.25%, 0.10%, and 0.15%, respectively. The incorporation of fibers in asphalt mixtures implies lower rut depths after 5000 cycles. In comparison to the control HMA, a decrease in the rut depth is observed in fiber-asphalt mixtures, about 22.14%, 15.36%, and 9.64% for basalt, glass, and steel fiber, respectively, which consequently enhances flexible pavement resistance against rutting. The microstructure analysis showed the difference in the mixture’s diameters, surface properties, and random fiber dispersion. Therefore, this dispersion contributed to creating a three-dimensional network, which improved the behaviour of HMA.